Prevention of Sudden Cardiac Death in Hypertrophic Cardiomyopathy: What has Changed in The Guidelines? - Reis,Liliana (2018)
Abstract Background: The new European Society of Cardiology guidelines for hypertrophic cardiomyopathy (HCM) define the estimation of sudden cardiac death (SCD) risk as an integral part of clinical management. An implantable cardioverter defibrillator (ICD) is recommended (class IIa) when the risk is ≥ 6%. Objectives: To compare the SCD risk stratification according to the 2011 and 2014 recommendations for ICD implantation in patients with HCM. Methods: Retrospective study including 105 patients diagnosed with HCM. The indication for ICD was assessed using the 2011 and 2014 guidelines. Statistical analysis was performed using SPSS software version 19.0.0.2®. The tests performed were bilateral, considering the significance level of 5% (p < 0.05). Results: Regarding primary prevention, according to the 2011 ACCF/AHA recommendations, 39.0% of the patients had indication for ICD implantation (level of evidence IIa). Using the 2014 guidelines, only 12.4% of the patients had an indication for ICD implantation. Comparing the two risk stratification models for patients with HCM, we detected a significant reduction in the number of indications for ICD implantation (p < 0.001). Of the 41 patients classified as IIa according to the 2011 recommendations, 68.3% received a different classification according to the 2014 guidelines. Conclusion: Significant differences were found when comparing the SCD risk stratification for ICD implantation in the two guidelines. The current SCD risk score seems to identify many low-risk patients who are not candidates for ICD implantation. The use of this new score results in a significant reduction in the number of ICD implanted.